Detection of Serum-Specific IgE by Fluoro-Enzyme Immunoassay for Diagnosing Type I Hypersensitivity Reactions to Penicillins - Ariza Veguillas, Adriana; Mayorga Mayorga, Cristobalina; Bogas Herrera, Gádor; Gaeta, Francesco; Salas, María; Valluzzi, Rocco Luigi; Labella, Marina; Pérez-Sánchez, Natalia Isabel; Caruso, Cristiano; Molina, Ana; Fernández-Duarte, Tahía Diana; Torres-Jaén, María Josefa; et al. (IOAP-MPDI, 2022)
Diagnosis of type I hypersensitivity reactions (IgE-mediated reactions) to penicillins is based on clinical history, skin tests (STs), and drug provocation tests (DPTs). Among in vitro complementary tests, the fluoro-enzyme immunoassay (FEIA) ImmunoCAP® (Thermo-Fisher, Waltham, MA, USA) is the most widely used commercial method for detecting drug-specific IgE (sIgE). In this study, we aimed to analyze the utility of ImmunoCAP® for detecting sIgE to penicillin G (PG) and amoxicillin (AX) in patients with confirmed penicillin allergy. The study includes 139 and 250 patients evaluated in Spain and Italy, respectively. All had experienced type I hypersensitivity reactions to penicillins confirmed by positive STs. Additionally, selective or cross-reactive reactions were confirmed by DPTs in a subgroup of patients for further analysis. Positive ImmunoCAP® results were 39.6% for PG and/or AX in Spanish subjects and 52.4% in Italian subjects. When only PG or AX sIgE where analyzed, the percentages were 15.1% and 30.4%, respectively, in Spanish patients; and 38.9% and 46% in Italian ones. The analysis of positive STs showed a statistically significant higher percentage of positive STs to PG determinants in Italian patients. False-positive results to PG (16%) were detected in selective AX patients with confirmed PG tolerance. Low and variable sensitivity values observed in a well-defined population with confirmed allergy diagnosis, as well as false-positive results to PG, suggest that ImmunoCAP® is a diagnostic tool with relevant limitations in the evaluation of subjects with type I hypersensitivity reactions to penicillins
Keywords: Alergia-Diagnóstico; Allergy diagnosis; Drug allergy; IgE; Immunologic tests